Peningkatan Perekonomian Masyarakat Melalui Industri Kreatif Jambu Kristal Sebagai Olahan Dodol di Desa Karangdoro Kecamatan Tegalsari Kabupaten Banyuwangi - Mahmudah Mahmudah; M Alaika Nasrulloh; Zulfi Zumala Dwi A (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2018)
The purpose of this community assistance is to increase communitywealth through the creative industry by utilizing guava Kristal c grade to be Dodol inKarangdoro village Banyuwangi. The method used in this community assistance is(PAR) participatory action research method with the approach and doing the trainingof utilization of guava Kristal grade c, guava Kristal that have bad shape butconsumable. This kind of guava Kristal is usually used as livestock feed or dumped bypeople. This training is given to mums, the member of PKK, Posyandu cadre, and groupof religious study. This training is named DJ KRIIS, the abbreviation of Dodol JambuKristal that become healthy snacks and can be made as a souvenir; therefore it canincrease community income.